New Ternary Compounds of the Composition Cu2SnTi3 and Their Crystal Structures - Sheng-Fang Huang; Yen-Cheng Chang; Po-Liang Liu (Applied Sciences, 2020)
A new ternary compound Cu2SnTi3 has been synthesized by vacuum sintering at 900 °C. The atomic structures of CaCu5- and InNi2-like Cu2SnTi3 are calculated using density functional theory methods. The X-ray diffraction (XRD) analysis and selected area diffraction (SAD) patterns of the new ternary compound Cu2SnTi3 are considered to verify the atomic structures of CaCu5- and InNi2-like Cu2SnTi3. The results reveal that the InNi2-like Cu2SnTi3 model has the lowest total energy of −35.239 eV, representing the trigonal crystal structure. The orthorhombic crystal structure of the CaCu5-like Cu2SnTi3 model has the second lowest total energy of −33.926 eV. Our theoretical X-ray diffraction peak profiles of InNi2-like (CaCu5-like) Cu2SnTi3 are nearly identical to experimental one, leading to an error below 2.0% (3.0%). In addition, the hexagonal crystal structure of the CaCu5-like Cu2SnTi3 model has the highest total energy of −33.094 eV. The stability of the Cu2SnTi3 in terms of energy follows the order: the trigonal, orthorhombic, and hexagonal crystal structure.